Understanding the Effects of Cancer-Related Factors on the Association Between Physical Activity and Quality of Life in Breast Cancer Survivors - Erica Schleicher; Wendy Demark-Wahnefried; Gregory Pavela; Kevin Fontaine; Nataliya Ivankova; Maria Pisu; Michelle Y. Martin; Yu-Mei Schoenberger-Godwin; Robert A. Oster; Kelly Marie Kenzik; Laura Q. Rogers (Journal of Physical Activity and Health, 2026)
Background : Breast cancer survivors often experience physical and mental side effects posttreatment, compromising their quality of life (QoL). The increasing number of survivors coping with long-term side effects creates public health concerns, emphasizing the need for supportive interventions. Although physical activity (PA) benefits cancer survivors, few studies examine the effect that cancer-related factors have on the relationship between PA levels and QoL among breast cancer survivors. Understanding the associations that cancer-related factors may have on the QoL response to PA is crucial for developing effective interventions. Methods : Baseline data from 341 postprimary treatment breast cancer survivors enrolled in a web-based diet and/or exercise intervention randomized controlled trial were analyzed. PA measures included accelerometry and self-reported moderate to vigorous PA (MVPA). QoL was assessed using Patient-Reported Outcomes Measurement Information System (PROMIS) global QoL and EuroQOL-5D-5L questionnaires. Pearson correlation coefficient tests and multiple linear regression assessed associations between MVPA and QoL and whether cancer-related factors moderated these associations. Results : The EuroQOL-5D-5L QoL index (and 4 out of 5 domains) showed statistically significant associations with self-reported MVPA. PROMIS physical health was correlated with both MVPA measures. Survivors > 24 months postdiagnosis had stronger associations between accelerometry-measured MVPA levels and EuroQOL-5D-5 L QoL index ( β = 0.0004, P = .003). Survivors receiving hormone therapy exhibited stronger associations between self-reported MVPA levels and PROMIS-physical health QoL domain compared with those not ( β = 0.0121, P = .028). Conclusion : Greater MVPA was modestly associated with better QoL, with stronger associations observed in survivors receiving hormone therapy or >24 months postdiagnosis. There are potential QoL benefits in implementing interventions immediately postdiagnosis and tailoring to treatment histories.